A Critical Analysis on the Social Determinants of Health in Disabled Population - Rommel Maglaya (Journal La Medihealtico, 2021)
This paper addresses the social determinants of health affecting the disabled population. It is considered that the prevalence of disability among the general adult population is significant. Furthermore, this paper presents a comprehensive analysis to identify the key social determinants which are highly applicable to health inequities and inequalities. Correspondingly, recommendations are critically proposed and laid out to address the issues impacting the given population. The health interventions and stakeholders involved are also critically examined to provide a broader perspective on the issue.